2005
DOI: 10.1083/jcb.200412022
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of starvation-induced and constitutive autophagy in Atg7-deficient mice

Abstract: Autophagy is a membrane-trafficking mechanism that delivers cytoplasmic constituents into the lysosome/vacuole for bulk protein degradation. This mechanism is involved in the preservation of nutrients under starvation condition as well as the normal turnover of cytoplasmic component. Aberrant autophagy has been reported in several neurodegenerative disorders, hepatitis, and myopathies. Here, we generated conditional knockout mice of Atg7, an essential gene for autophagy in yeast. Atg7 was essential for ATG con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

96
2,105
6
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,202 publications
(2,222 citation statements)
references
References 50 publications
96
2,105
6
15
Order By: Relevance
“…Recently, it has been observed that the hepatocytes of liver-specific conditional Atg7 KO mice develop ubiquitin-positive aggregates. 14 We also observed such aggregates in Atg5 À/À neonates (unpublished data). These findings suggest that baseline autophagy is critical for intracellular clearance ( Figure 3).…”
Section: Intracellular Clearance By 'Baseline Autophagy': Antidegenermentioning
confidence: 52%
“…Recently, it has been observed that the hepatocytes of liver-specific conditional Atg7 KO mice develop ubiquitin-positive aggregates. 14 We also observed such aggregates in Atg5 À/À neonates (unpublished data). These findings suggest that baseline autophagy is critical for intracellular clearance ( Figure 3).…”
Section: Intracellular Clearance By 'Baseline Autophagy': Antidegenermentioning
confidence: 52%
“…Similar to the systemic atg7 KO mice, ATG5i mice on dox appeared smaller in size with smaller weight gain in both genders (Figure 1(c)). Anatomical inspection revealed, as in the whole-body somatic atg7 KO mice and/or atg5 and atg7 KO mice, a reduction of fat [16] and muscle tissues (Figures 1(d,e)) [17], with the presence of hepatomegaly [9], splenomegaly, and seminal vesicle atrophy (Figure 1(fh)) [18]. …”
Section: Resultsmentioning
confidence: 99%
“…This coincides with a period of metabolic stress wherein neonates must adapt and engage the autophagic machinery to mobilise their own food stores [8,9]. Additionally, conditional whole-body knockout of Atg7 in adult mice has provided further evidence for the requirement of autophagy to survive acute metabolic stress.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that autophagosome formation plays a critical anti-apoptosis role during PPRV infection. Moreover, the expression products of the ATG7 and Beclin-1 genes are essential for the activation of autophagosome formation, and knocking down the ATG7 and Beclin-1 genes can impair the autophagic pathway [70,71]. Interestingly, Beclin-1 is required for ATG7-dependent and ATG7-independent autophagy [72].…”
Section: Discussionmentioning
confidence: 99%